Complete structural characterisation of the human aryl hydrocarbon receptor gene. Issue 1 (February 1996) - Bennett, P; Ramsden, D B; Williams, A C
Abstract : Aims —To clone and characterise the complete structural gene for the human aryl hydrocarbon receptor (AhR). This gene, located on chromosome 7, encodes a cytosolic receptor protein which, upon activation by various xenobiotic ligands, translocates to the nucleus, where it acts as a specific transcription factor. Methods —Primers, based on the AhR cDNA sequence, were used in conjunction with recently developed long range PCR techniques to amplify contiguous sections of the cognate gene. The amplicons produced were then cloned and characterised. A cDNA probe was also used to screen a human P1 library. Results —Using the cDNA primers, DNA fragments which mapped the entire coding region of the gene were amplified and cloned. All but one of these fragments were amplified directly from human genomic DNA. The remaining fragment was amplified using DNA prepared from a P1 clone as the PCR template. This P1 clone, obtained by screening a human P1 library, also contained the entire Ah locus. Characterisation of amplified and cloned DNA fragments provided sufficient information for the construction of a complete structural map of the gene. This also included 150 base pairs of nucleotide sequence data at all intronic termini. Conclusions —These data indicate that the human AhR gene is about 50 kilobases long and contains 11 exons. The overall intron/exon structure of the human gene is homologous to that of the previously characterised mouse gene; however, it is probably some 20 kilobases larger. These results demonstrate the need for further characterisation and provide the data to facilitate this.